2015
DOI: 10.1088/0067-0049/218/2/27
|View full text |Cite
|
Sign up to set email alerts
|

GRAVITY-MODE PERIOD SPACINGS AS A SEISMIC DIAGNOSTIC FOR A SAMPLE OF γ DORADUS STARS FROM KEPLER SPACE PHOTOMETRY AND HIGH-RESOLUTION GROUND-BASED SPECTROSCOPY

Abstract: Gamma Doradus stars (hereafter γ Dor stars) are gravity-mode pulsators of spectral type A or F. Such modes probe the deep stellar interior, offering a detailed fingerprint of their structure. Four-year high-precision space-based Kepler photometry of γ Dor stars has become available, allowing us to study these stars with unprecedented detail. We selected, analyzed, and characterized a sample of 67 γ Dor stars for which we have Kepler observations available. For all the targets in the sample we assembled high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 41 publications
10
114
4
Order By: Relevance
“…The five stars color coded in blue are bona fide γ Dor pulsators. Right: as in left panel, with overplotted the location of ≈300 γ Dor stars analyzed by Bruntt et al (2008), Catanzaro et al (2011), Fossati et al (2011), Tkachenko et al (2012, Bradley et al (2015), and Van Reeth et al (2015) and some hybrid γ Dor-δ Sct stars from Catanzaro et al (2011) and Tkachenko et al (2012). broadening of spectral lines (Aerts et al 2009). If indeed turbulent pressure fluctuations excite high-order modes, a connection with γ Dor may be present as well, which could involve finite amplitude pressure fluctuations in the HCZ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The five stars color coded in blue are bona fide γ Dor pulsators. Right: as in left panel, with overplotted the location of ≈300 γ Dor stars analyzed by Bruntt et al (2008), Catanzaro et al (2011), Fossati et al (2011), Tkachenko et al (2012, Bradley et al (2015), and Van Reeth et al (2015) and some hybrid γ Dor-δ Sct stars from Catanzaro et al (2011) and Tkachenko et al (2012). broadening of spectral lines (Aerts et al 2009). If indeed turbulent pressure fluctuations excite high-order modes, a connection with γ Dor may be present as well, which could involve finite amplitude pressure fluctuations in the HCZ.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the stars that present a non-negligible macroturbulent broadening lie predominantly along this same area of the sHR diagram. As a matter of fact, all the stars listed in Table A.1 and HD 37594 are indeed bona fide γ Dor pulsators (Díaz-Fraile et al 2014;Van Reeth et al 2015).…”
Section: The γ Dor Instability Stripmentioning
confidence: 93%
See 1 more Smart Citation
“…When these modes show clear multiplets, the core rotation rate can be determined. Period spacings have been detected in dozens of γ Dor stars (Van Reeth et al 2015a), but only a small number have evident rotational splittings . Some γ Dor stars also show p modes, which are sensitive to conditions at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the high-precision photometric observations of space missions such as Kepler (Koch et al 2010), such period spacing patterns were recently found in some γ Doradus stars (e.g., Chapellier et al 2012;Kurtz et al 2014;Bedding et al 2015;Van Reeth et al 2015b;Keen et al 2015;Saio et al 2015). They have since been used to probe the rotation rates (e.g, Murphy et al 2016;Van Reeth et al 2016;Ouazzani et al 2017;Sowicka et al 2017;Guo et al 2017) and the nature of the mixing processes (e.g., Schmid & Aerts 2016) in the deep interior of these stars.…”
Section: Introductionmentioning
confidence: 96%